What is the effect of paracetamol (acetaminophen) ingestion on exercise performance? Current findings and future research directions - Grgic, J. (Sports Medicine, 2022)
In recent years, studies have explored the effects of paracetamol (acetaminophen) ingestion on exercise performance. However, due to the contrasting findings, there is still no consensus on this topic. This article provides an overview of the effects of paracetamol on endurance, sprinting, and resistance exercise performance. Studies have reported that paracetamol ingestion may be ergogenic for endurance performance. These effects occur when paracetamol is ingested 45-60 min before exercise and appear to be more pronounced in time-to-exhaustion versus time-trial tests. Besides endurance, paracetamol ingestion 30 min before exercise increases mean power during repeated cycling sprints in interval training involving repeated 30-s all-out bouts. Preliminary data on paracetamol ingestion also suggest: (a) improved endurance performance in the heat; (b) an improvement in single sprint performance, at least when paracetamol is ingested following exercise-induced fatigue; and (c) attenuation of the decline in muscular strength that occurs with repeated maximum contractions. An ergogenic effect of paracetamol is most commonly observed when a dose of 1500 mg is ingested 30-60 min before exercise. Despite these performance-enhancing effects, the aim of this article is not to promote paracetamol use, as side effects associated with its consumption and ethical aspects need to be considered before utilizing paracetamol as an ergogenic aid. Future research on this topic is still needed, particularly related to paracetamol dosing, timing of ingestion, and the effects of paracetamol in females and elite athletes.